Gino Strada, a man I was lucky to meet - Contini, Sandro (Acta Biomedica Atenei Parmensis, 2021)
I met Gino Strada in 2004 at its office in Milan, after my first mission with Emergency in Sierra Leone, and few weeks later, during a very successful and fascinating conference in Piacenza. I was proud to be there. Gino knew how to speak to the people and how to rise emotions, enthusiasms and sense of humanity, telling the war tragedies encountered during his life dedicated to the victims of war and violence. [read more clicking on pdf]